2022
DOI: 10.1111/jog.15349
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous abortion among Toxoplasma gondii IgG seropositive women: Molecular detection, genotype identification, and serological assessment with conventional ELISA and avidity ELISA

Abstract: ObjectivesIt has been generally believed that women who exposed to Toxoplasma gondii before pregnancy and have anti‐T. gondii IgG antibody are immunized and their newborns will be protected from congenital infection. This study is aimed to investigate the role of T. gondii infection in spontaneous abortion through serological and molecular methods in southern Iran.Study designBlood samples were taken from 50 spontaneously aborted mothers and anti‐T. gondii antibodies were assessed using conventional enzyme‐lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…This paper concluded that chronic T. gondii infection may be one of the major worldwide causes of miscarriage. A recent report of chronically infected women with high avidity infection showed that parasite DNA was detectable in blood and placental samples from spontaneous abortions, suggesting that congenital infection was a possibility in these women with chronic toxoplasmosis 48 . A recent systematic review and meta‐analysis reported that recent T. gondii infection is associated with an elevated risk of spontaneous abortion, confirming our results 49 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This paper concluded that chronic T. gondii infection may be one of the major worldwide causes of miscarriage. A recent report of chronically infected women with high avidity infection showed that parasite DNA was detectable in blood and placental samples from spontaneous abortions, suggesting that congenital infection was a possibility in these women with chronic toxoplasmosis 48 . A recent systematic review and meta‐analysis reported that recent T. gondii infection is associated with an elevated risk of spontaneous abortion, confirming our results 49 …”
Section: Discussionsupporting
confidence: 90%
“…A recent report of chronically infected women with high avidity infection showed that parasite DNA was detectable in blood and placental samples from spontaneous abortions, suggesting that congenital infection was a possibility in these women with chronic toxoplasmosis. 48 A recent systematic review and meta-analysis reported that recent T. gondii infection is associated with an elevated risk of spontaneous abortion, confirming our results. 49 Miscarriages appear to be the most well-studied adverse pregnancy outcome in the previous research, and preterm birth has not been well characterized in women with latent toxoplasmosis.…”
Section: Discussionsupporting
confidence: 90%
“…gondii infection, while T . gondii infection is usually asymptomatic (latent) among immunocompetent individuals, [ 7 , 12 ]. Like humans, the laboratory rat ( Rattus norvegicus ) is resistant to T .…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompromised individuals, the infection could have life-threatening sequels, such as toxoplasmic encephalitis, myocarditis, or disseminated infections [ 7 , 8 ]. Congenital toxoplasmosis is also a life-threatening condition which may lead to abortion, stillbirth, and preterm birth [ 9 12 ]. The intensity of T .…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that women who have T. gondii IgG before pregnancy are immunized against congenital toxoplasmosis [ 2 ]. However, our recent reports revealed that T. gondii IgG-seropositive women also had a risk of spontaneous abortion [ 35 ]. On the other hand, some epidemiologic studies suggest an association between abortion and breast cancer risk, but the results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%